Differentiated HT22 cells as a novel model for in vitro screening of serotonin reuptake inhibitors - Lim, Juhee; Bang, Yeojin; Kim, Kyeong-Man; Choi, Hyun Jin (Frontiers in Pharmacology, 2023)
The mouse hippocampal neuronal cell line HT22 is frequently used as an in vitro model to investigate the role of hippocampal cholinergic neurons in cognitive functions. HT22 cells are derived from hippocampal neuronal HT4 cells. However, whether these cells exhibit the serotonergic neuronal phenotype observed in mature hippocampal neurons has not been determined yet. In this present study, we examined whether the differentiation of HT22 cells enhances the serotonergic neuronal phenotype, and if so, whether it can be used for antidepressant screening. Our results show that differentiation of HT22 cells promoted neurite outgrowth and upregulation of N-methyl-D-aspartate receptor and choline acetyltransferase, which is similar to that observed in primary cultured hippocampal neurons. Furthermore, proteins required for serotonergic neurotransmission, such as tryptophan hydroxylase 2, serotonin (5-hydroxytryptamine, 5-HT)1a receptor, and serotonin transporter (SERT), were significantly upregulated in differentiated HT22 cells. The transcription factor Pet-1 was upregulated during HT22 differentiation and was responsible for the regulation of the serotonergic neuronal phenotype. Differentiation also enhanced the functional serotonergic properties of HT22 cells, as evidenced by increase in intracellular 5-HT levels, SERT glycosylation, and 5-HT reuptake activity. The sensitivity of 5-HT reuptake inhibition by venlafaxine in differentiated HT22 cells (IC50, 27.21 nM) was comparable to that in HEK293 cells overexpressing SERT (IC50, 30.65 nM). These findings suggest that the differentiation of HT22 cells enhances their functional serotonergic properties, and these cells could be a potential in vitro system for assessing the efficacy of antidepressant 5-HT reuptake inhibitors.